2019
DOI: 10.3390/brainsci9020037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Management of HIV-Associated Cognitive Impairment: Experience from a Multidisciplinary Memory Service for People Living with HIV

Abstract: As the HIV population ages, the prevalence of cognitive impairment (CI) is increasing, yet few services exist for the assessment and management of these individuals. Here we provide an initial description of a memory assessment service for people living with HIV and present data from a service evaluation undertaken in the clinic. We conducted an evaluation of the first 52 patients seen by the clinic. We present patient demographic data, assessment outcomes, diagnoses given and interventions delivered to those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
(46 reference statements)
1
30
0
Order By: Relevance
“…Gender, education, marital status, current CD4 count and hospital stay were included in the model based on previous studies showing them to be consistent predictors for neurocognitive impairment. [25][26][27][28][29][30][31][32] The logistic regression model was statistically significant, χ2 (9) = 72.91. The model explained 35.0% (Nagelkerke R 2 ) of the variance in neurocognitive impairment status and correctly classified 75.8% of cases.…”
Section: Factors Associated With the Neurocognitive Impairment: A Mulmentioning
confidence: 91%
“…Gender, education, marital status, current CD4 count and hospital stay were included in the model based on previous studies showing them to be consistent predictors for neurocognitive impairment. [25][26][27][28][29][30][31][32] The logistic regression model was statistically significant, χ2 (9) = 72.91. The model explained 35.0% (Nagelkerke R 2 ) of the variance in neurocognitive impairment status and correctly classified 75.8% of cases.…”
Section: Factors Associated With the Neurocognitive Impairment: A Mulmentioning
confidence: 91%
“…The mechanism of this brain pathology can be a result of opportunistic infections of the brain or primary HIV encephalopathy, where HIV affects the brain directly [87]. The degree of cognitive impairment may range from very mild to full-blown AIDS dementia complex (ADC) [99]. ADC is usually seen at advanced symptomatic stages and is associated with low CD4+ T cell count.…”
Section: Other Viruses and The Brainmentioning
confidence: 99%
“…Neuroimaging studies of HIV patients have found that the frontal lobes, striatum, and hippocampi are particularly impacted [100]. Cognitive impairment in HIV encephalopathy is associated with a range of symptoms, including mood and personality changes, executive deficit, memory impairment, and motor/psychomotor slowing [99].…”
Section: Other Viruses and The Brainmentioning
confidence: 99%
“…Gender, education, marital status, current CD4 count and hospital stay were included in the model based on previous studies showing them to be consistent predictors for HAND (18)(19)(20)(21)(22)(23)(24)(25). The logistic regression model was statistically signi cant, χ2(9) = 72.91.…”
Section: Factors Associated With the Neurocognitive De Cit: A Multivamentioning
confidence: 99%